Audit Committee Quality and Internal Control: An Empirical Analysis - Krishnan, Jayanthi (The Accounting Review, 2005)
I examine the association between audit committee quality and the quality of corporate internal control. While information on the quality of internal control is not generally available, companies changing auditors are required to disclose any internal control problems that were pointed out by their predecessor auditors. The empirical results are based on a comparison of companies disclosing such internal control problems with a control sample of companies changing auditors but not disclosing internal control problems. Audit committee quality is measured in three dimensions: its size, its independence, and its expertise. The internal control problems are observed at two levels of increasing seriousness: reportable conditions and material weaknesses. The sample time period precedes the effective dates of recent policy changes regarding audit committees. The results indicate that independent audit committees and audit committees with financial expertise are significantly less likely to be associated with the incidence of internal control problems. This is true for both levels of internal control problems. The results are consistent with recent policy emphasis on audit committee independence and expertise.